MicroRNA-484 / Akt axis in the regulation of breast cancer cells sensitivity to antitumor drugs - O. E. Andreeva; D. V. Sorokin; A. M. Scherbakov; Y. Y. Shchegolev; M. V. Gudkova; M. A. Krasil’nikov (Успехи молекулярной онкологии, 2022)
The development of acquired resistance of malignant tumors to specific drugs, such as target and hormonal drugs, is usually associated with a rearrangement of the intracellular signaling network and activation of unblocked growth pathways. Epigenetic regulators, in particular, non-coding miRNAs that control the level of expression of specific signaling proteins, are directly involved in the development and maintenance of such changes. We have previously shown that the development of resistance of breast cancer cells to mTOR (mammalian target of rapamycin) inhibitors and hormonal drugs is accompanied by constitutive activation of protein kinase Akt, the key anti-apoptotic protein.Aim. To study the role of microRNAs in the regulation of Akt expression and the formation of a resistant phenotype of breast cancer cells.We have shown that Akt activation in the tamoxifen- or rapamycin-resistant MCF-7 sublines is associated with a decrease in the level of miRNA-484, one of the Akt suppressors. Transfection of microRNA-484 into MCF-7 cells does not affect the activity of estrogen signaling, but leads to a marked decrease in Akt expression and is accompanied by an increase in cell sensitivity to tamoxifen and rapamycin. The obtained data demonstrate the involvement of the miRNA-484 / Akt axis in the breast cancer cells’ sensitization to target and hormonal drugs, which allows us to consider miRNA-484 as a potential candidate for drug development to cure resistant cancers.